Evaluation of some laboratory parameters and their diagnostic and prognostic role in COVID-19 patients admitted to Syrian hospitals - Mohammed Akkari; Rawaa AL-Kayalia; Ali Ibrahima (Zagazig Journal of Pharmaceutical Sciences, 2023)
A serious threat to global health is posed by COVID-19, particularly to the health system in Syria, which has been decimated by the protracted war. COVID-19 in Syria has resulted in a significant number of cases that need hospitalization and intensive monitoring. COVID-19 causes a multisystem failure of many organs, mainly, heart disease. Therefore, our study aims to evaluate the role of inflammatory laboratory parameters and cardiac enzymes of COVID-19 patients at several phases of follow-up in order to evaluate their importance in deciding whether patients will be remained to the hospital or discharged. The study included the measurement Ferritin, CRP, CK-MB and AST levels in 45 COVID-19 patients in two hospitals in Syria and 30 volunteers as a control group. This study found that odds ratio (OR) for CRP was the highest among the studied indicators. Ferritin levels were different between the surviving and deceased patients in the admission sample, and there was a significant difference between ferritin and CRP at the admission and discharge samples for the patients who were still alive. Interestingly, 42.2% of patients had elevated CK-MB and AST levels that were higher than normal values. The most crucial criterion for the diagnosis of COVID-19 infection was CRP, while ferritin was the most significant signal for the prognosis of death.